Application of Portable Spectroscopic Tools in the Exploration of Manganese Oxide Minerals: Preliminary Results from the Case Study of Drama Mn-Oxide Deposits, Northern Greece - George Soulamidis; Marjolene Jatteau; Christina Stouraiti; Panagiotis Voudouris; Constantinos Mavrogonatos; Konstantinos Soukis; Cécile Fabre; Marie-Camille Caumon; Jean Cauzid; Alexandre Tarantola (Materials Proceedings, 2023)
In situ analysis techniques of ore and drill core samples provide fast results that can be used to facilitate the decision-making process during the geochemical exploration of ore deposits. This study applies the use of two portable devices, pXRF and Laser-Induced Breakdown Spectroscopy (pLIBS), to a small manganese oxide deposit situated in the Rhodope metamorphic complex, Kato Nevrokopi, northern Greece. The study provides an example of exploration of a variety of manganese minerals, including Mn-oxides, Mn-carbonates, and Mn-silicates. It tests the accuracy of mineral identification using these two techniques. The application of pXRF helped in the elemental identification of critical trace metals in certain Mn minerals and showed that there is Ag enrichment in the ore, which is associated with the mineral hetaerolite (ZnMn2O4). From the LIBS analysis, it can be seen that Mn minerals with different Mn valences (+2, +3, and +4) display distinct spectra. This observation will be further examined by expanding the sampling pool of the spectra of manganese oxides. It is postulated that the presence of trace elements in Mn minerals may differ according to the valence of the Mn, which in turn affects the LIBS signals of the sample.